Bioclimatic analyses of distributions of a parasitoid Peristenus digoneutis and its host species Lygus spp. in Europe and North America. (13th September 2012) - Haye, Tim; Olfert, Owen; Weiss, Ross M.; Gariepy, Tara D.; Broadbent, Bruce; Kuhlmann, Ulrich
<x xml:space="preserve">Abstract</x> 1 Peristenus digoneutis Loan is a parasitoid of Lygus plant bugs, which was successfully introduced from Europe into North America in the 1980s for controlling native Lygus populations. Surveys confirmed that P. digoneutis populations have become established throughout eastern North America and that the spread of the parasitoid continues. For unknown reasons, previous releases of P. digoneutis in Western Canada were not successful. 2 A bioclimate (climex®; Hearne Scientific Software Pty Ltd, Australia) model for P. digoneutis in North America was developed, based on climate and ecological parameters, and then validated with actual distribution records. The current distribution of P. digoneutis in eastern North America was consistent with the predicted distribution. The model suggests that P. digoneutis will probably continue its spread westwards throughout the U.S.A. along the Great Lakes. 3 The southern distribution of P. digoneutis is expected to be limited by hot summer temperatures, whereas its northern range is limited by the number of Lygus host generations rather than cold stress. 4 Peristenus digoneutis has the potential to occur in the southern parts of the prairie ecozone of western Canada; however, Ecoclimatic Index values in the prairies indicate mainly marginal or unfavourable conditions, which may explain why earlier releases of P. digoneutis in Western Canada failed.